Evaluating the seagrass ecological condition and habitat extent in Karimunjawa National Park, Jepara Indonesia - Kusnadi, Agus; Alifatri, La Ode; Chamidy, Ardian Nurrasyid; Rasyidin, Asep; Sobirin, Sobirin (Jurnal Kelautan Tropis, 2024)
In the coastal ecosystem, seagrass meadows play a vital role in delivering ecosystem services such as provision, control, and support. However, this ecosystem is one of the most threatened in the coastal environment, and it has been degraded as a result of anthropogenic disturbance and rapid environmental changes. Furthermore, the extent of the seagrass meadows is unknown, and the health of the meadows is unmonitored and unrecorded. There is little information on the current state of the seagrass extent and health conditions in Karimunjawa National Park. We evaluate the abundance, states, and health conditions of the seagrass meadows based on the ecological quality index in Karimunjawa National Park, Jepara, Indonesia. This district has a vast extent of seagrass meadows but has been affected by the expansion of the industrial/tourism area within the region. This study aimed to assess the seagrass current condition based on the ecological quality index. The result showed that the total seagrass extent area in Karimunjawa National Park was 969,15 ha where seven species were found in this area, including Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Cymodocea serrulate, Halodule pinifolia, Halophila ovalis and Halodule uninervis. Seagrass meadow coverages were moderate and categorized as less healthy. The seagrass ecological quality index value was 0.66 which indicated that the seagrass condition in Karimunjawa National Park was moderate. Ecological factors that affect the seagrass state are epiphyte cover and macroalgal cover.